The Action of Cathepsin D in Human Articular Cartilage on Proteoglycans - Sapolsky, Asher I. (1973)
In recent years the lysosomal cathepsins have been implicated as important agents in the physiological degradation of various cartilages. In the present study, the nature of cathepsin present in human articular cartilage was investigated by microtechniques and a possible role for cathepsins in the cartilage degradation observed in osteoarthritis was sought. The results of this study indicated that the hemoglobin and proteoglycan-digesting activity in the human cartilage observed is predominantly that of a cathepsin D-type enzyme. This cathepsin D-type enzyme activity was present in two to three times greater amounts in yellowish or ulcerated articular cartilage from patients with primary osteoarthritis than in control “normal” human cartilages. The human cathepsin D-type enzyme, as well as a highly purified cathepsin D from bovine uterus degraded proteoglycan subunit (PGS) maximally at pH 5. Both enzyme preparations were inactive on hemoglobin at pH 6-8, but degraded PGS considerably at neutral pH. The activity of the human cathepsin extract was not affected by reagents which inhibit or activate cathepsins A and B. Neutral proteases which are active on hemoglobin or are inhibited by diisopropylfluorophosphate (DFP) were not detected in these preparations, but contamination by another type of neutral protease cannot be excluded. Chloroquine inhibited the degradation of PGS at neutral pH by the human cartilage enzyme extract.